In Silico and in Vitro Studies of Fluorinated Chroman-2-Carboxilic Acid Derivatives as an Anti-tubercular Agent - Kapadiya Khushal M.; Jadeja Yashwantsinh S.; Banik Avishek; Khunt Ranjan C. (Folia Medica, 2018)
Background: Despite the use of traditional method, Ugi reaction currently is a well-established multicomponent reaction. Chromane motif itself possesses a variety of biological functions. In order to improve its anti-tubercular activity, it is necessary to modify it accordingly.